THREE DIMENSIONAL EXPLICIT MODEL FOR COMETARY TAIL IONSINTERACTIONSWITH SOLAR WIND - Al Bermani, M J F; Alhamed, S A; Khalaf, S Z; Ali, H Sh; Selman, A A (Al-Nahrain Journal of Science, 2018)
The different interactions between cometary tail and solar wind ions are studied in the present paper based on three-dimensional Lax explicit method. The model used in this research is based on the continuity equations describing the cometary tail-solar wind interactions. Three dimensional system was considered in this paper. Simulation of the physical system was achieved using computer code written using Matlab 7.0. The parameters studied here assumed Halley comet type and include the particle density , the particles velocity v, the magnetic field strength B, dynamic pressure p and internal energy E.The results of the present research showed that the interaction near the cometary nucleus is mainly affected by the new ions added to the plasma of the solar wind, which increases the average molecular weight and result in many unique characteristics of the cometary tail. These characteristics were explained in the presence of the IMF.